Expression of miR-15a and miR-16-1 in patients with chronic lymphocytic leukemia - Humplikova, Lenka; Kollinerova, Sona; Papajik, Tomas; Pikalova, Zuzana; Holzerova, Milena; Prochazka, Vit; Divoka, Martina; Modriansky, Martin; Indrak, Karel; Jarosova, Marie (Biomedical papers, 2013)
Introduction: MicroRNAs (miRNAs) are small non-coding single-stranded RNA molecules that regulate gene expression at the post-transcriptional level. In the pathogenesis of chronic lymphocytic leukemia (CLL), miR-15a and miR-16-1 play an important role. These miRNAs are located on chromosome 13 in the 13q14.3 region, which is deleted in more than 55% of CLL patients. This aberration affects expression of miRNAs.Objectives: The study aimed at performing a molecular genetic analysis of miR-15a and miR-16-1 expression in a group of 39 patients diagnosed with CLL and determining the association between the expression of the two miRNAs and types of deletions in the 13q14 region.Methods: We used fluorescence in situ hybridiziation (FISH) for determination of mono- or biallelic deletion 13q and quantitative polymerase chain reaction (Q-RT-PCR) to revealed expression miR-15a and miR-16-1 in 39 patients suffering from CLL.Results: The analysis comprised 19 patients with monoallelic 13q14 deletion, 3 patients with biallelic deletion, 9 patients with both monoallelic and biallelic deletions, and 8 patients without 13q14 deletion serving as controls. The results showed different levels of miRNA expression in individual patients. Significantly higher normalized levels of miR-15a expression were found in the control group and patients with monoallelic 13q14 expression compared with patients with biallelic deletion. There was a significantly decreased expression of both miRNAs in patients with biallelic deletion of the 13q14 region but only when deletions were present in 77% or more of cells, as detected by fluorescent in situ hybridization (FISH).
Keywords: chronic lymphocytic leukemia; microRNA; miRNA expression; fluorescence in situ hybridization; 13q14 deletion; monoallelic deletion; biallelic deletion